G. Boole, Not J. M. Keynes, Is the Founder of the Logical Approach to Probability - BRADY, Michael (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
A fundamental and basic error committed by all economists and philosophers doing work on Keynes is their failure to realize that the original, logical theory of probability, with the consequent emphasis placed on relational, propositional logic, imprecise probability and interval valued approaches to decision making, was developed by George Boole and not by J. M. Keynes. All one needs to do is read chapters I, II and X to XVII of Keynes’s 1921 A Treatise on Probability and compare Keynes’s chapters with chapters I, XI, XII and XVI to XXI of Boole’s The Laws of Thought. A shorter route to this conclusion is to skip all but chapter I of Boole and compare it with chapter I of Keynes. Why no social scientist, behavioral scientist, economist, or philosopher has been able to do this simple task is a question that needs to be investigated by psychologists and psychiatrists looking for problems related to cognitive dissonance. A careful reader of chapters I and II of Keynes’s A Treatise on Probability will soon realize that Keynes is talking explicitly about Boole’s logical, objective, probability relation. This relation has absolutely nothing to do with Plato’s theory of forms. How do we come to know this relationship? Boole states that we come to know this relationship through both observation (empirical) and reflection (intuition or perception). This paper shows that there is a deep Boole-Keynes connection that has been overlooked in the literature on Keynes. Keynes built his logical theory of probability on Boole. One can extend Hishiyama’s 1969 conjecture, about Keynes’s A Treatise on Probability not having been read by any economist, to also conclude that Boole’s The Laws of Thought was not read by any other economist except Keynes.